Pregnant Women's Experiences with Sleep Disturbances in the Third Trimester - Dirgahayu, Ingrid; Rustikayanti, R.Nety; Jayanti, Tri Nur (CV. Global Health Science Group, 2024)
Hormonal and physiological changes affect a woman's ability to sleep, especially during pregnancy. Changes in steroid sex hormones and gonadotropins during the first trimester and the additional physical discomfort associated with foetal growth during the second and third trimesters are obvious reasons for sleep disturbances. Describe and interpret the perspectives of pregnant women who experience complaints or sleep disorders that affect sleep quality during pregnancy. The research method used was qualitative with a phenomenological approach. Recruitment of participants was carried out by purposive sampling. The criteria for participants in this study are: third trimester pregnant women with sleep complaints who can communicate well, are not on medication and are physically and mentally healthy. The number of participants in this study was 9 participants until data saturation. Data analysis was conducted after each participant had collected data. Interview transcripts and field notes were analysed. Specific analysis techniques were used using the selective or high-leverage approach. The most common physical complaints felt by pregnant women are lower back pain, a growing belly, frequent urination at night and hot flashes being the most common complaints. Emotional disturbances during the third trimester of pregnancy such as anxiety, mood disorders, and discomfort can greatly affect the quality of sleep of pregnant women. The combination of psychological and physiological factors during the third trimester of pregnancy can create significant challenges to sleep quality. Therefore, it is important to provide emotional support, provide access to healthcare, and teach pregnant women appropriate stress management strategies.